Case report: Bullous pemphigoid associated with sintilimab therapy for pMMR/MSS colorectal cancer - Wang, Ting; Shao, Qianwen; Xiao, Chunmei; Liu, Lianke (Frontiers in Oncology, 2023)
Immunotherapy has become a very effective treatment for many cancers. It has a unique set of immune system-related adverse effects, collectively known as immune-related adverse events (irAEs). Skin toxicities are the most common irAEs, of which bullous pemphigoid, although rare, is potentially life-threatening and affects patients' survival. In this article, we report the treatment of bullous pemphigoid caused by programmed cell death protein-1 (PD-1) in a case of proficient mismatch repair (pMMR)/microsatellite stable (MSS) colorectal cancer. Methylprednisone was tapered to 4mg twice a day and no significant adverse effects were observed in the patient. No new skin lesions occurred recently in the patient and the original skin lesions healed. In particular, the patient's immunotherapy was not stopped and the best outcome was a partial remission of the disease, lasting for more than eight months.